Pengaruh Gaya Kepemimpinan dan Kompensasi terhadap Kinerja Karyawan Kalenan Cafe dan Resto Sawahan Nganjuk - Windy Cahya Putri; Dyah Suswanti Respatiningtias; Muhammad Bawono (Jurnal Ekonomi Manajemen Akuntansi, 2025)
Employee performance is a key factor in the operational success of a business, including at Kalenan Cafe & Resto Sawahan Nganjuk, which is growing in the culinary sector. The low performance of some employees is suspected to be influenced by suboptimal leadership styles and a compensation system that is not transparent and fair. This study aims to examine the effect of leadership style on employee performance; the effect of compensation on employee performance; and the simultaneous effect of leadership style and compensation on employee performance. The study employed a quantitative survey approach with 65 employees selected using simple random sampling. Data were collected through questionnaires and documentation related to performance, leadership, and compensation, and analyzed using multiple linear regression. The results indicate that leadership style has a positive and significant effect on employee performance, while compensation has a negative yet significant effect. Simultaneously, leadership style and compensation significantly influence performance. Therefore, implementing a participative leadership style that supports two-way communication and a fair compensation system is essential to enhance employee motivation and performance, as well as to create a productive, harmonious work environment that supports business growth.